Ileo-colic Intussusception Associated with Pathological Lead Point Non-Hodgkin’s Lymphoma that Involved the Caecum: Report of a Case (Jalalabad Medical Journal, 2025)
Adult intussusception is a sparse condition. The causes of adult intussusception are disparate from those of children. In adults, the probability of pathological lead points and surgical treatment is immensely recommended. We draw a case report of non-Hodgkin’s lymphoma that caused ileo-colic intussusception in an elderly female. The patient was admitted to our hospital due to recurrent and unresolved abdominal pain for 5 months, and a CT scan revealed consistent with ileo-colic intussusception. The patient had to undergo a limited right hemicolectomy and was diagnosed with non-Hodgkin’s lymphoma that involved the caecum. Surgeons should consider intestinal neoplasms as a potential lead point of intussusception in adults and should need urgent, adequate surgical intervention.Jalalabad Med J 2024; 21 (2); 73-75